Regulating industrial chemicals: lessons for U.S. lawmakers from the European Union’s REACH Program - Abelkop, Adam D.K.; Botos, Agnes; Wise, Lois R.; Graham, John D. (Bloomington, 2012)
"The REACH regulation in Europe is a unique product of the European system and European political compromises, so that REACH would be very difficult to replicate in the United States. There are no substantial discussions about doing so in the United States today. Thus, any lessons learned from REACH would be much more helpful if they were directed to the TSCA reform proposals actually being discussed in the United States rather than to the report's hypothetical effort to replicate REACH. The report's recommendations for ways to simplify REACH fail to analyze the impact of the proposals on the overall effectiveness of REACH in view of its comprehensive chemicals policy objectives."